2019
DOI: 10.1101/808337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress-induced dendritic branching inC. elegansrequires both common arborization effectors and stress-responsive molecular pathways

Abstract: Stress influences the shape of dendritic arbors in neurons. During the stress-induced dauer stage of Caenorhabditis elegans, the IL2 neurons arborize to cover the anterior body wall. In contrast, the FLP neurons arborize to cover the anterior body wall during non-dauer development.Previous work showed that the membrane-bound receptor DMA-1 regulates FLP branching as part of a larger protein complex. Using forward genetics, we show that the IL2 neurons also use the DMA-1 complex to regulate branching. To unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For example, in Drosophila , IRE1’s RIDD activity is essential for differentiation of the photoreceptor cells 31 . In C elegans , IRE1 deficiency prevents normal dendrite branching in touch‐sensing neurons 32 and interferes with dendrite remodeling during developmental adaptation of the worm to harsh environment 33 . Similarly, the anticipatory nature of UPR target induction is not unique to plasma cells.…”
Section: Upr Signaling Pathways Are Tightly Integrated With Development and Physiologymentioning
confidence: 99%
“…For example, in Drosophila , IRE1’s RIDD activity is essential for differentiation of the photoreceptor cells 31 . In C elegans , IRE1 deficiency prevents normal dendrite branching in touch‐sensing neurons 32 and interferes with dendrite remodeling during developmental adaptation of the worm to harsh environment 33 . Similarly, the anticipatory nature of UPR target induction is not unique to plasma cells.…”
Section: Upr Signaling Pathways Are Tightly Integrated With Development and Physiologymentioning
confidence: 99%
“…While many of the molecular mechanisms that control PVD neurite branching have been identified, it is unknown whether other highly branched C. elegans neurons are governed by similar mechanisms. However, in addition to PVD neurons, studies have shown that depletion of the DMA-1 receptor complex components and associated proteins, including DMA-1, MNR-1, LECT-2, HPO-30, TIAM-1, and ACT-4/Actin, causes reduced branching phenotypes in FLP neurons, although these neurons have distinct branching architectures during development (Liu and Shen, 2011 ; Salzberg et al, 2013 ; Díaz-Balzac et al, 2016 ; Androwski et al, 2019 ; Tang et al, 2019 ; Figure 1A ). Moreover, a proprotein convertase KPC-1/Furin, originally identified as a negative regulator of the DMA-1 complex pathway, was shown to promote both PVD and FLP branching by adjusting dendritic DMA-1 levels (Salzberg et al, 2014 ; Dong et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…KPC-1 is also required for the dendritic arborization of IL2 neurons, specifically induced during dauer stages (Schroeder et al, 2013 ). Recently, it was shown that the DMA-1 complex components are also required for IL2 arborization during dauer stages (Androwski et al, 2019 ). Therefore, it is likely that different neurons utilize similar DMA-1 receptor complexes to modulate dendrite morphogenesis; however, individual ligand-receptor complex components may differ.…”
Section: Introductionmentioning
confidence: 99%